Convergent validity of the international physical activity questionnaire (IPAQ): meta-analysis. - Kim Y; Park I; Kang M; Kim, Youngdeok; Park, Ilhyeok; Kang, Minsoo (Public Health Nutrition, 2013)
Objective: The purpose of the present study was to use a meta-analytic approach to examine the convergent validity of the international physical activity questionnaire (IPAQ).Design: Systematic review by meta-analysis.Setting: The relevant studies were surveyed from five electronic databases. Primary outcomes of interest were the product-moment correlation coefficients between IPAQ and other instruments. Five separate meta-analyses were performed for each physical activity (PA) category of IPAQ: walking, moderate PA (MPA), total moderate PA (TMPA), vigorous PA (VPA) and total PA (TPA). The corrected mean effect size (ESρ) unaffected by statistical artefacts (i.e., sampling error and reliability) was calculated for each PA category. Selected moderator variables were length of IPAQ (i.e., short and long form), reference period (i.e., last 7 d and usual week), mode of administration (i.e., interviewer and self-reported), language (i.e., English and translated) and instruments (i.e., accelerometer, pedometer and subjective measure).Subjects: A total of 152 ESρ across five PA categories were retrieved from twenty-one studies.Results: The results showed small- to medium-sized ESρ (0.27-0.49). The highest value was observed in VPA while the lowest value was found in MPA. The ESρ were differentiated by some of the moderator variables across PA categories.Conclusions: The study shows the overall convergent validity of IPAQ within each PA category. Some differences in degree of convergent validity across PA categories and moderator variables imply that different research conditions should be taken into account prior to deciding on use of the appropriate type of IPAQ.